Students Language Attitudes Towards Acehnese Language: a Study on the Retention and Threat of Regional Language Extinction - Hayati, Cut Intan; Fahrurrazi, Fahrurrazi; Iqbal, Muhammad; Wahdaniah, Wahdaniah (ALACRITY : Journal of Education, 2025)
Language attitudes play a vital role in maintaining or threatening the sustainability of a language. This study examines the language attitudes of students towards the Acehnese language by focusing on the potential for preservation and the threat of extinction of regional languages. The research was conducted on 400 students from 8 Islamic boarding schools in Lhokseumawe City and North Aceh who were randomly selected, including 4 modern dayahs and 4 traditional dayahs. Using Garvin and Mathiot's theory of language attitudes, this study evaluated three main aspects: language fidelity, language pride, and awareness of language norms. With the Mix Method approach, qualitative data is analyzed to provide in-depth descriptions, while quantitative data is processed using SPSS for statistical analysis. The results showed that the attitude of speaking Acehnese was positive, with average scores in the aspects of loyalty (67%), pride (59%), and awareness (66%). Interestingly, traditional dayah shows a higher level of language retention than modern dayah, with percentages of loyalty (73%), pride (63%), and awareness (72%). On the contrary, modern dayah students show lower scores in these three aspects. This research reinforces the importance of language preservation efforts through a community-based approach and education, as well as a reminder that language is a cultural bridge, not just a means of communication.